Repercussions of child cancer in the daily life of a family caregiver - Eduarda Gayoso Meira Suassuna de Medeiros; Rosana Farias Batista Leite; Déborah Karollyne Ribeiro Ramos; Layze Amanda Leal Almeida (Rev Rene)
It aims at investigating the effects of cancer diagnosis in the everyday life of families whose children have neoplasm. This is a qualitative study with exploratory-descriptive focus, with semi-structured interview as a tool for gathering information. The research was conducted at the University Hospital and the Institute of Paraiba Against Cancer, both located in Campina Grande/Paraíba, Brazil, between July and September 2012. The empirical material was analyzed following proposed content analysis. Results showed that the quality of social life, psychological symptoms and personal growth were affected. We concluded that caring for a relative with neoplasm, especially if this is a child, it is a challenge for the family. However, it is possible to build good experiences living with the sick child and face the disease as an opportunity for personal growth.